Effects of Lactic and Ascorbic Acid Treatments on Proximate Composition and Shelf-Life of Sundried Oreochromis Niloticus Fillet - Muteti , Martha K.; Manguya, Lusega D.; Sabwa , Ani J. (African Journal of Education,Science and Technology (AJEST), 2015)
Tilapia Oreochromisniloticus is a perishable commodity and its quality and freshness declines rapidly after death as a result of poor handling lowering its shelf-life and nutritive value which is highly needed by the fast growing world population. This study was therefore carried out to determine the proximate composition and shelf life of sun-dried Nile Tilapia (Oreochromisniloticus) treated with various concentrations of lactic acid and ascorbic acids (3%, 5% and10%) for a duration of six weeks(42 days). Fish samples with average weight of 226.5 ±84.8g, and average total length of 24.7±3.6 cm were obtained from the University of Eldoret fish farm; they were de-scaled, eviscerated, washed and rinsed in a large amount of water. Muscle sample of fish were divided into groups. Group A. (1, 2, 3) were treated with 3%, 5% and10 %, of lactic acid respectively. Group B. (4,5, and 6) were treated with 3%, 5% and 10% ascorbic acid respectively and Group C, without any treatment (control group). Triplicate samples were used for each treatment. The fillets were then soaked in treatments for 30 minutes then dried under the sun in an artificial cage made from locally available materials. After 1 day, 5 days, 2 weeks, 4 weeks and 6 weeks of drying, moisture content, crude protein and crude lipid levels were determined. Data obtained was then analyzed using MINITAB statistical software. The results revealed a significant reduction in moisture content in all the samples from 77.9±1.65% of fresh fillet to 2.6±0.98% of the control. This was as a result of solar drying effect. It was also observed that crude protein and lipids increased in treated samples but reduced in control samples which were attributed to the ability of the preservatives to retard deterioration of protein and lipids in O. niloticusfillets. There was no significant difference (p>0.05) in proximate composition of samples treated with different concentrations of lactic acid. This was also evident in samples treated with different concentrations of ascorbic acid. Results in the study also revealed that effects of equal concentrations of lactic and ascorbic acids on proximate composition of Nile O. niloticus had no significant difference. However, means of crude lipids and protein at the end of the study, registered a significant difference (p<0.05) between lactic and ascorbic acid, ascorbic acid with overall high crude protein and lipids. It is concluded that solar drying resulted to more stable Nile Tilapia fillets, with higher proteins and lipids. A treatment of 10 % ascorbic acid combined with open hygienic solar drying is therefore recommended so as to reduce post-harvest losses, increase shelf life of Tilapia products and make available high nutritive products with little health side effects, to the ever growing human populations.